Industry 4.0 and Global Businesses : a Multidisciplinary Investigation - Yakut, Enis (Emerald Publishing Limited, 2022)
Industry 4.0 and Global Businesses: A Multidisciplinary Investigationprovides a multidisciplinary perspective on the transformative effects of Industry 4.0 by aggregating original theoretical, conceptual, and empirical research.- Resumé vydavatel